THE COMPARISON OF EVIDENCE IN STATE ADMINISTRATIVE COURT BETWEEN INDONESIA AND SOUTH KOREA - Dalimunthe, Fadli Zaini (Jurnal Hukum dan Peradilan, 2020)
The judiciary under the supreme court consists of general courts, religious courts, military courts, and state administrative courts. In each procedural law court, the provisions concerning evidence are regulated. Evidence is the stage where the parties try to convince the panel of judges about the truth of the arguments put forward in a dispute based on valid evidence. Evidence has an important role because the results of evidence can be the basis for consideration by the panel of judges in making a decision. Evidence in the procedural law of the state administrative court is not only carried out in the Indonesian state administrative court but also in the South Korean Administrative Court. The historical development and organizational structure of the South Korean Administrative Court are the basis for analyzing the Evidence in the South Korean Administrative Court. Lessons from the South Korean Administrative Court can see the similarities and differences in the concept of evidence and type of evidence used in the South Korean Administrative Court with the Indonesian State Administrative Court. The approach used in this study is the statutory approach, comparative approach, and conceptual approach.